Gastroprotective Effectiveness Test of 70% Ethanol Extract of Karamunting Leaves on White Male Rats (Rattus norvegicus) - Saru Noliqo Rangkuti; Nuraini Nuraini; Melisa (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Gastritis is a health disorder in digestion, especially the stomach. Treatment of gastritis can be cured by using medicinal plants which are thought to have compounds that are efficacious as gastroprotective. The karamunting plant is one of the biodiversity that must be developed because the karamunting plant has one of the properties as a gastroprotective. Karamunting, among others, has various kinds of ingredients such as flavonoids, saponins, tannins, alkaloids, and triterpenoids which are useful as herbal medicines. Objective: This study aims to determine the content of secondary metabolites, determine the effectiveness of healing gastritis in rats and determine what dose of 70% ethanol extract of karamunting leaves has the effectiveness of gastroprotective healing in rats. Method: Test animals were divided into 6 groups consisting of group I negative control CMC 0.5%; group II positive control of 500mg/5ml sucralfate; group III induction control 1000mg/kgBB; groups IV, V, VI 70% ethanol extract of karamunting leaves at a dose of 20mg/200g BW of rats, a dose of 40mg/200g BW of rats and a dose of 60mg/200g BW of rats. After the treatment, the animals were dissected and the stomach was observed macroscopically. Result: Data were analyzed with the Kruskal Wallis test, and followed by the Mann-Whitney test. The results of this study showed that 70% ethanol extract of karamunting leaves has effectiveness as a gastroprotective. A dose of 20mg/200gBW rats has a % protection value of 76%, a dose of 40mg/200gBW rats has a % protection value of 75%, and a dose of 60mg/200gBW rats has a % protection value of 100%. Statistical test results showed that there was a significant difference in each group on gastroprotective effectiveness (p <0.05). Conclusion: The conclusion of this study was that the 70% ethanol extract of caramunting leaves had the most optimal gastroprotective effectiveness at dose III, namely 60mg/200gBW rats.